Evaluation of New Antimicrobial Agents Based on tris(1H-Indol-3-yl)methylium Salts: Activity, Toxicity, Suppression of Experimental Sepsis in Mice - Alexey S. Trenin; Elena B. Isakova; Michael I. Treshchalin; Vasilisa A. Polozkova; Elena P. Mirchink; Alexey A. Panov; Alexander Y. Simonov; Olga P. Bychkova; Victor V. Tatarskiy; Sergey N. Lavrenov (Pharmaceuticals, 2022)
The antimicrobial activity and toxicity of three novel synthetic antibacterial agents containing tris(1H-indol-3-yl)methylium fragment were studied in vitro and in vivo. All compounds in vitro revealed high activity (minimal inhibitory concentration (MIC) 0.13–1.0 µg/mL) against bacteria that were either sensitive or resistant to antibiotics, including multidrug-resistant clinical isolates. The derivatives combining high antimicrobial activity with relatively low cytotoxicity against human donor fibroblasts HPF-hTERT were subjected to further testing on mice. In vivo they revealed fairly good tolerance and relatively low toxicity. Acute toxicity was evaluated, and the main indicators of toxicity, including LD50 and LD10, were determined. A study of compounds in vivo showed their efficiency in the model of staphylococcal sepsis in mice. The efficiency of compounds may be due to the ability of indolylmethylium salts to form pores in the cytoplasmic membrane of microbial cells and thereby facilitate the penetration of molecules into the pathogen.